Pengaruh Pendekatan Problem Posing dengan Model Pembelajaran Kooperatif Tipe Stad terhadap Kemampuan Komunikasi Matematis Siswa Kelas Xii Sma Negeri 1 Salo Kabupaten Kampar - Astuti Astuti (LPPM Universitas Pahlawan Tuanku Tambusai, 2015)
The students’ communication ability of mathematical about linear program material of SMA Negeri 1 Salo Kampar was low. It needs improvement on the learning system which is done by the teachers. This research was conducted at analyzing the influence of Learning Approach of Problem Posing Through Cooperative Learning Model STAD in communication ability of mathematical of student’ capability high initial and capability low initial.